Eksistensi Kewenangan Komisi Pemberantasan Korupsi Terhadap Eksekusi Putusan Tindak Pidana Korupsi Berdasarkan Ketentuan Hukum Yang Berlaku - Salmon, Harly Clifford Jonas; Purwanto, Astrid Hilarry; Lyshandra, Angelia Hilarry (MATAKAO Corruption Law Review, 2024)
Introduction: Corruption is like a disease that arises one after another that can bring destruction to economic, political, socio-cultural, and state security aspects. Purposes of the Research: Analyze the KPK's authority to execute corruption verdicts based on applicable legal provisions. Methods of the Research: The research method used in this paper is normative legal research or library legal research, and a statutory approach and conceptual approach. The sources of legal materials used are primary and secondary legal materials. The technique of collecting legal materials is through literature study, namely by searching for legal materials by reading, seeing and listening and searching the internet, then the data will be analyzed using objective theories related to the relationship between variables which are then described to solve the problem which is the purpose of this research. Results of the Research: Prior to the amendment of the law on KPK, the authority and duties of the institution were regulated in Article 6 letter c of Law No. 30 of 2002 on KPK. Then based on Article 50 of Law Number 48 of 2009 concerning Judicial Power Jo Article 1 paragraph 1. Article 8 paragraph 1 and Article of Law Number 16 of 2004 concerning the Prosecutor's Office of the Republic of Indonesia Jo Article 270 of the Criminal Procedure Code, it is explained that the executor is the authority of the prosecutor under the Supreme Court, both in general cases and special criminal cases. It is also stated that if the KPK exercises the authority to execute the corruption court decision, then the KPK has exceeded the limits of its authority so that the execution violates the principle of legality or is invalid and null and void. Juridically, the Attorney General's Office is the only institution authorized by law to execute court decisions that have permanent legal force.